TERRITORIAL UNITS COMPETITIVENESS: A SELF-RELIANT CONCEPT OR A DERIVATIVE CONCEPT OF FIRMS COMPETITION? - Nikolaos Kapitsinis; Theodore Metaxas; Marie Noelle Duquenne (European Regional Science Association (ERSA), 2011)
In the modern globalized economy there are some concepts which are very important for the current socio-economic system. One of them is competition. Though in classical political economy, the economic realm, with competition as its centerpiece, seems to be carrying it over all other fields, today competition appears as the sole immanent category imbuing all aspects of everyday life. So, in current globalised economic background, competition has been extended in fields of education, health, wealth fare and among them, the spatial sciences and economic geography - competition among territorial units (cities, regions or states) in order to attract financial and human capital. The concept of territorial competitiveness was introduced in scientific and policy affairs almost 30 years ago and mainly during the last 15 years it has been the basis of territorial development policy. The scientific discussion regarding this concept is very rich since many authors, councils and organisations have put forward an opinion having articulated three particular approaches: the defending one which supports it, the critical one which disputes it and the neutral approach. The deep review of the three approaches and the role of territorial competitiveness in current territorial development policy contribute to a global view of the concept. This paper makes efforts to examine thoroughly the concept of competition in its relationship with space, if it direct or not, evaluating the existing theoretical propositions, participating in the discussion which takes place about territorial competitiveness with many interesting opinions expressed by economists, planners and geographers, exercising influence in decision making. It first focuses on the question whether territorial units competition is a self-reliant concept or a concept which is derivative of firms competition. Secondly, one of the basic aspects regarding territorial competitiveness is the comparison between the way that the firms and the territories behave mainly in case of bad economic performance and even bankruptcy. Within this context the cases of Greece and Dubai present remarkable interest regarding their behaviour after their bad economic performance.
Keywords: 330; competitiveness; territorial unit; firms; bankruptcy; Greece; Dubai